Candidate Experience in Participating in Virtual Recruitment on Candidate Satisfaction and Trust: A Study at State-Owned Enterprises (PLN) - Hasriani; Altri Wahida; Halim Usman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of candidate experience in participating in virtual recruitment on candidate satisfaction and trust at PT PLN (Persero), with the background of increasing use of digital recruitment systems in State-Owned Enterprises, which requires companies to ensure that virtual selection processes are able to provide a good experience for candidates. This study uses a quantitative approach with a simple linear regression analysis technique through SPSS on candidates who have participated in PT PLN (Persero) virtual recruitment. The results show that candidate experience affects candidate satisfaction, while candidate experience does not affect candidate trust. Overall, this study confirms that the success of virtual recruitment depends on the company’s ability to create experiences that can increase candidate satisfaction. Therefore, improvements are needed in communication quality, transparency, and the stability of the digital recruitment system at PT PLN (Persero).